Association of orthostatic blood pressure with the symptoms of orthostatic hypotension and cognitive impairment in patients with multiple system atrophy. (May 2020) - Ueda, Miki; Nakamura, Tomohiko; Suzuki, Masashi; Imai, Eriko; Harada, Yumiko; Hara, Kazuhiro; Hirayama, Masaaki; Katsuno, Masahisa
Highlights: We investigated orthostatic hypotension (OH) symptom in multiple system atrophy (MSA). Mean blood pressure (BP) at 60° tilt < 80 mmHg is related to orthostatic symptoms. Standing mean BP < 80 mmHg is associated with cognitive impairment in MSA with OH. White matter lesions did not correlate with either BP or BP decrease at 60° tilt. Abstract: The degree and frequency of orthostatic hypotension (OH) are high in patients with multiple system atrophy (MSA); however, the association of orthostatic blood pressure (BP) with the symptoms of OH and cognitive impairment in these patients remains unclear. The aim of this study was to clarify whether absolute BP and/or changes in BP during standing are related to OH symptoms and cognitive impairment in patients with MSA. Thirty-two patients with MSA were examined using the head-up tilt and cognitive function tests. OH symptoms were evaluated using a patient-reported scale. The results were compared with those for 15 age- and sex-matched healthy controls. Seventeen of the 32 (53.1%) patients had OH, with eight of them exhibiting OH symptoms, which were related to the absolute BP value at 60° tilt. However, OH symptoms were not related to the degree of decrease in BP during the tilt test, and they were frequently observed in patients with a mean BP of <80 mmHg at 60° tilt (sensitivity, 67%; specificity, 91%). Cognitive dysfunction assessed by the Mini-Mental State Examination (MMSE; ≤ 26) was also associated with a low mean BP at 60° tilt (odds ratio, 1.32; 95% confidence interval, 1.04–1.67; p = 0.02). The upright BP value is associated with OH symptoms and the MMSE score in patients with MSA. Thus, careful observation of OH symptoms can enable early management of BP and the detection of cognitive impairment in these patients.